Diseño de un manual de funciones que permita eficiencia en el establecimiento de tareas del personal de la empacadora finca “Señor de Andacocha”, provincia Santo Domingo de los Tsáchilas 2014 - Montes Sud, José Isaac (2015)
This research was made in Ecuador in the province of Santo Domingo de los Tsáchilas Region Santo Domingo, which allowed to make a design manual functions to generate efficiency in establishing staff tasks baler Farm Señor de Andacocha. This research work is effected with the use of scientific methods that contributed to the process of analysis and interpretation of data collected with of purpose of establish findings at a general level.Is conducted for all staff of the baler. And as a result it was observed that all respondents agreed with the importance of using a manual functions for realization of their activities. The staff of this organization have no knowdedge of driving a manual functions on the basis that at no time was presented to them a manual to be guided and to make their work within the entity and prevent the execution specific tasks to the position held .. Also, the staff is limited to conduct their t activities that are mandated by their immediate superior on this farm Señor de Andacocha skills and profile requerements or a position is not specified, and those who work in it meet the specific requerements of deposition.